Intravenous immunoglobulin as a preventive strategy against BK virus viremia and BKV‐associated nephropathy in kidney transplant recipients—Results from a proof‐of‐concept study. Issue 1 (27th August 2020) - Benotmane, Ilies; Solis, Morgane; Velay, Aurélie; Cognard, Noëlle; Olagne, Jérôme; Gautier Vargas, Gabriela; Perrin, Peggy; Marx, David; Soulier, Eric; Gallais, Floriane; Moulin, Bruno; Fafi‐Kremer, Samira; et al.
Abstract : BK virus (BKV) replication occurs frequently in kidney transplant recipients (KTR), potentially leading to BKV‐associated nephropathy (BKVAN) and graft loss. Patients with high titers of BKV‐neutralizing antibodies (NAbs) are protected against BKV replication, and intravenous immunoglobulin (IVIg) infusion can increase NAb titers. We investigated whether early IVIg administration prevents BKV replication in patients with low NAb titers (<4 log10 against the BKV‐specific genotype). Based on NAb titers on the day of transplantation, KTR followed in the Strasbourg University Hospital (n = 174) were retrospectively divided into the following 3 risk categories for BKV replication: (1) patients with low NAb titers ("high‐risk") who received IVIg for the first 3 posttransplant months (n = 44), (2) patients with low NAb titers ("high‐risk") who did not undergo IVIg treatment (n = 41), and (3) patients with high NAb titers ("low‐risk") who did not receive IVIg (n = 89). At 12 posttransplant months, the incidence of BKV viremia in the high‐risk group treated with IVIg (6.8%) was similar to that observed in the low‐risk group (10.1%) and markedly lower than that of the untreated high‐risk group (36.6%; P  < .001). Similar results were observed with regard to BKVAN. We conclude that IVIg may be a valuable strategy for preventing BKV replication. Abstract : This proof‐of‐concept study suggests that intravenous immunoglobulin may be a valuable therapeutic to prevent BK virus viremia and BKV‐associated nephropathy in kidney transplant recipients at high risk of BKV replication.